Activity-Based Cost Analysis of Including Contrast-Enhanced Ultrasound (CEUS) in the Diagnostic Pathway of Focal Pancreatic Lesions Detected by Abdominal Ultrasound - Faccioli, Niccolò; Dietrich, Christoph F.; Foti, Giovanni; Santi, Elena; Comai, Alessio; D’Onofrio, Mirko (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To perform an activity-based cost analysis of the inclusion of contrast-enhanced ultrasound (CEUS) in the diagnostic pathway of newly detected focal pancreatic lesions revealed by abdominal ultrasound (US) in comparison to computed tomography (CT) and magnetic resonance imaging (MRI).Materials and Methods Over a 14-year period, 977 patients with newly detected focal pancreatic lesions on US and subsequently studied with CEUS and/or CT and MRI were included. The cost of equipment, materials and human resources for every imaging method was calculated. We analyzed the costs in different scenarios considering whether or not CT or MRI was required in the diagnostic pathway. The savings (R) were calculated by subtracting the differential cost of CEUS from the eliminated third-level exam (CCEUS: CEUS cost; CCT: CT cost; CMRI: MRI cost) compared to conventional ultrasound (CCEUS-CUS): R = CCT-(CCEUS-CUS) or R = CMRI-(CCEUS-CUS).Results Total costs were: US 28.39 €; CEUS 70.50 €; CT 106.23 €; MRI 219.61 €. In 388/563 patients CEUS characterized the pancreatic lesion as solid, with only CT being performed as a second-level investigation: the savings were 68 870.36 €. In 266/414 patients CEUS diagnosed lesions as cystic, with only MRI being performed as a second-level examination: the savings were 16 825.07 €. Considering the whole diagnostic pathway of the patients, the cost savings were 76 809.35 € for solid lesions and 26 242.49 € for cystic lesions, with overall savings of 103 051.84 €.Conclusion CEUS represents a cost-effective imaging method for the differentiation of focal pancreatic lesions and could guide the selection of the best imaging modality for preoperative assessment, thereby optimizing resources and securing the diagnostic pathway.
Keywords: pancreas; activity-based cost analysis; CEUS